Relationships between resource availability and elevation vary between metrics creating gradients of nutritional complexity - Lee, Mark A.; Burger, Grace; Green, Emma R.; Kooij, Pepijn W. [UNESP] (Springer Nature, 2021)
Plant and animal community composition changes at higher elevations on mountains. Plant and animal species richness generally declines with elevation, but the shape of the relationship differs between taxa. There are several proposed mechanisms, including the productivity hypotheses; that declines in available plant biomass confers fewer resources to consumers, thus supporting fewer species. We investigated resource availability as we ascended three aspects of Helvellyn mountain, UK, measuring several plant nutritive metrics, plant species richness and biomass. We observed a linear decline in plant species richness as we ascended the mountain but there was a unimodal relationship between plant biomass and elevation. Generally, the highest biomass values at mid-elevations were associated with the lowest nutritive values, except mineral contents which declined with elevation. Intra-specific and inter-specific increases in nutritive values nearer the top and bottom of the mountain indicated that physiological, phenological and compositional mechanisms may have played a role. The shape of the relationship between resource availability and elevation was different depending on the metric. Many consumers actively select or avoid plants based on their nutritive values and the abundances of consumer taxa vary in their relationships with elevation. Consideration of multiple nutritive metrics and of the nutritional requirements of the consumer may provide a greater understanding of changes to plant and animal communities at higher elevations. We propose a novel hypothesis for explaining elevational diversity gradients, which warrants further study; the ‘nutritional complexity hypothesis’, where consumer species coexist due to greater variation in the nutritional chemistry of plants.
Keywords: Altitude; Biodiversity; Forage; Grassland; Protein